Identifiability: A Predictive Quantitative Measure for the Comparison of a Task Designed in Different Interaction Styles. - Christou, Georgios.; Jacob, Robert J. K. (Tufts University. Tisch Library., 2017)
This paper presents a predictive quantitative measure for the comparison of the performance of a task, when that task is designed in different interaction styles. The paper presents an extension of Task Knowledge Structures (Johnson and Johnson, 1991a) and based on this extension it presents identifiability, which is the evaluative and predictive measure that is the main focus of the paper. The paper then presents an experiment, which provides evidence towards the validity of the measure and its intended usage.